Developing illustrative descriptors of aspects of mediation for the Common European Framework of Reference (CEFR): A Council of Europe project. (31st May 2016) - North, Brian; Piccardo, Enrica
Abstract : The notion of mediation has been the object of growing interest in second language education in recent years. The increasing awareness of the complex nature of the process of learning – and teaching – stretches our collective reflection towards less explored areas. In mediation, the immediate focus is on the role of language in processes like creating the space and conditions for communication and/or learning, constructing and co-constructing new meaning, and/or passing on information, whilst simplifying, elaborating, illustrating or otherwise adapting input in order to facilitate the process concerned. At a deeper level though, the notion of mediation embraces a broader spectrum of dimensions and connotations. Mediation has been defined as a 'nomadic notion' (Lenoir1996 ) insomuch as it is at the core of a variety of scientific disciplines and the term 'mediation' is used in different senses in different contexts.